2009
DOI: 10.3189/002214309788608868
|View full text |Cite
|
Sign up to set email alerts
|

Surface topography of Dome A, Antarctica, from differential GPS measurements

Abstract: Dome A is the highest ice feature in Antarctica, at over 4000 m a.s.l., and overlies the Gamburtsev mountains. It is believed that deep ice-core drilling in this area may reveal the oldest ice in Antarctica, providing an unparalleled paleoclimate record in excess of 1 Ma, and perhaps going back as far as 1.2 Ma (Xiao and others, 2008). However, little is known about this area because its height and distance from the coast and scientific stations makes access difficult.Surface elevation information for the Dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 3 publications
0
20
1
2
Order By: Relevance
“…One study determined that the northern peak is the highest (Zhang et al 2007), whereas the other study suggested that the southern peak is ca. 0.3 m higher (Cheng et al 2009). However, we found that the two peaks have similar elevations.…”
Section: Surface Topography Of Dome Argusmentioning
confidence: 94%
See 1 more Smart Citation
“…One study determined that the northern peak is the highest (Zhang et al 2007), whereas the other study suggested that the southern peak is ca. 0.3 m higher (Cheng et al 2009). However, we found that the two peaks have similar elevations.…”
Section: Surface Topography Of Dome Argusmentioning
confidence: 94%
“…Previous studies have shown that on-going deep ice core drilling may provide a unique paleoclimate record extending to 1.2 Mya (e.g., Xiao et al 2008). In preparation for the project, the surface topography was investigated, and an AWS was deployed by the 21st CHINARE in the austral summer of 2004/05 (Zhang et al 2007;Cheng et al 2009;Ma et al 2010). Ice sheet thickness and bed topography were surveyed with ground-based ice-penetrating radar by the 24th CHINARE in 2007/08 (Bo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kunlun Station, where the ice thickness is the maximal of 3139 m and internal and basal ice deformation should be slight due to the flat and open floor of subglaical trough valley, meets desirable factors for deep ice core drilling well.Therefore, with the advantages of small snow accumulation rate [2], negligible horizontal ice flow velocity [3] and good weather conditions at Dome A [16], the location of Kunlun Station is suggested to perform the first deep ice core drilling in order to acquire high-resolution ice core records approach to a timescale of 1 Ma. Considering that some others factors influencing the timescale and location of deep ice core drilling, such as basal melting and environments, are still hard to determined exactly until now, during the drilling and research of the first deep ice core, in combination with numerical modeling, it is necessary to seek another one drilling site of deep ice core at Dome A so that the paleo-climatic records reach, even exceed 1.5 Ma.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Dome A深冰芯计划对于理解地球的环境变化具有重要意 义, 有助于理解: 1) 导致 150~120 万年前气候轨道周 期从 4 万年到 10 万年的转换原因 [3] ; 2) Dome C显示 的间冰期序列在 45 万年前出现强烈变化的原因. 目 前研究显示, Dome A具有地球表面最低的年平均气 温 [4] , 极低的近期积累率 [5] , 接近 0 的水平流速 [6] , 较 平坦的冰盖表面 [7] 和存在超过 3000 m冰厚, 满足深 冰芯钻探的必要条件 [4] . 冰盖内部等时层是雷达反射信号显示的冰盖内 部可区分的层状结构, 主要由冰盖内部的冰密度、冰 体酸度和冰晶组构变化所形成 [8] .…”
Section: 摘要unclassified